The lived experiences of cisgender openly gay Latino males as mid-level administrators in higher education in the southwest region of the United States - Valdez, Robert A., author; Kuk, Linda, advisor; Lynham, Susan A., committee member; Aragon, Antonette, committee member; DeMirjyn, Maricela, committee member (Colorado State University. Libraries, 2022)
The purpose of this narrative inquiry study was to explore the stories and experiences of openly gay Latino males who serve as mid-level administrators in higher education. This study focused on narrative stories of personal and historical context of the participants' intersecting identities that have implications for their daily interactions in an institutional environment. This study is significant in four ways. First, In the United States, gay Latinos have been subject to social oppression, invisibility, and misrepresentation throughout history. This lack of recognition and support stifles gay Latinos the ability to develop a sense of belonging. Narrative inquiry was used to increase awareness of the lived experiences of gay Latinos as administrators in higher education and gives them an opportunity to share their experiences. The key findings from the participants' narratives were the influences of family expectations, support systems, fear of discrimination or homophobia, and lack of representation in higher education. The struggles and achievements from these stories are valuable and can raise visibility for more inclusive leadership practices, mentorship, and equitable policies in higher education.